Low-Cost Organic Adsorbents for Elemental Mercury Removal from Lignite Flue Gas - Marta Marczak-Grzesik; Stanisław Budzyń; Barbara Tora; Szymon Szufa; Krzysztof Kogut; Piotr Burmistrz (Energies, 2021)
The research presented by the authors in this paper focused on understanding the behavior of mercury during coal combustion and flue gas purification operations. The goal was to determine the flue gas temperature on the mercury emissions limits for the combustion of lignites in the energy sector. The authors examined the process of sorption of mercury from flue gases using fine-grained organic materials. The main objectives of this study were to recommend a low-cost organic adsorbent such as coke dust (CD), corn straw char (CS-400), brominated corn straw char (CS-400-Br), rubber char (RC-600) or granulated rubber char (GRC-600) to efficiently substitute expensive dust-sized activated carbon. The study covered combustion of lignite from a Polish field. The experiment was conducted at temperatures reflecting conditions inside a flue gas purification installation. One of the tested sorbents—tire-derived rubber char that was obtained by pyrolysis—exhibited good potential for Hg0 into Hg2+ oxidation, resulting in enhanced mercury removal from the flue. The char characterization increased elevated bromine content (mercury oxidizing agent) in comparison to the other selected adsorbents. This paper presents the results of laboratory tests of mercury sorption from the flue gases at temperatures of 95, 125, 155 and 185 °C. The average mercury content in Polish lignite was 465 μg·kg−1. The concentration of mercury in flue gases emitted into the atmosphere was 17.8 µg·m−3. The study analyzed five low-cost sorbents with the average achieved efficiency of mercury removal from 18.3% to 96.1% for lignite combustion depending on the flue gas temperature.